Penguatan Kompetensi Pedagogik Guru Bahasa Inggris Dalam Meningkatkan Kualitas Pembelajaran Di MAN 3 Kabupaten Tasikmalaya - Euis Yulianti R; Yat Rospia Brata; Tatang Parjaman (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the implementation of pedagogic competencies in teaching and learning activities, the obstacles faced by educators in teaching and learning activities and the efforts made by educators to deal with these obstacles. This study uses a descriptive method with a qualitative approach. Qualitative research by exploring how the pedagogical competence of English teachers improves the quality of learning at MAN 3 Tasikmalaya. This study went through a research process in the form of reduction, data presentation, drawing conclusions and triangulation. The results of the study revealed that the educators had not fully mastered the characteristics of students both in terms of intellectual, emotional, physical, spiritual and moral. They are also not optimal in terms of group discussions and the use of educational media, but in the areas of academic potential analysis, effective learning and lesson planning the teacher have done well. Obstacles were also described in this study such as the lack of facilities and infrastructure that support the process of teaching and learning activities, the lack of reference book sources provided by the government, the lack of training or training held, the lack of motivation of students in learning English activities, especially in vocabulary and the understanding of educators is still low on the mastery of information technology that can support learning activities. This study also reveals efforts to overcome obstacles such as trying to maximize existing facilities and infrastructure, looking for other learning resources to add references to learning materials, trying to attend seminars or workshops organized by non-government, trying to motivate students to be more enthusiastic about participating English learning activities and continue learning to upgrade yourself to improve skills in information technology to support English learning activities. Although this research is quite detailed, qualitative research does not reach many parties due to the limited number of respondents.